(untitled) (Nepal Journal of Environmental Science, 2022)
Burmese Ferret Badger (Melogale personata) was recorded by camera trapping for the first time in Nepal’s Nagarjun forest of Shivapui Nagarjun National Park. According to IUCN, it was expected to inhabit only the eastern part of Nepal but recently the species has been recorded from central and western parts of the country. A globally rarely studied species was only observed during daylight in Nepal but this time it is photographed during the night. A Burmese Ferret Badger was captured for one event with three photographs with PCRI 0.085 in the dense mixed forest of Schima wallichii, Castanopsis indica. A more comprehensive study on its ecology is necessary to implement suitable conservation measures.